COMMUNICATION SKILLS FOR MANAGING ANGRY PATIENTS IN NURSING PRACTICE: AN EVIDENCE-INFORMED METHODOLOGICAL NARRATIVE REVIEW (Vietnam Journal of Community Medicine, 2026)
Background:  Angry/agitated patients are common in clinical practice and may lead to conflict and workplace violence.Objectives:  To synthesize evidence on patient anger, communication strategies, and de-escalation training in nursing.Methods:  An evidence-informed methodological narrative review was conducted in PubMed, Scopus, Web of Science, and CINAHL for studies published from January 2010 to 1 March 2026.Results:  De-escalation includes active listening, empathy, voice control, non-verbal communication, emotional self-regulation, and problem-solving. Training may improve short-term knowledge, attitudes, and confidence, whereas evidence for reducing actual violence remains inconsistent.Conclusions:  Communication skills are essential but must be combined with simulation, feedback, and organizational support
Keywords: Communication; Nurse-Patient Relations; Aggression; Workplace Violence; Professional Competence.